Formulating Indonesia’s Covid-19 Policy based on South Korea’s Experience - Rafikasari, Astri (International Journal of Humanities and Education Development (IJHED), 2020)
This paper aims to analyze the formulation of Indonesian policy in overcoming Covid-19. The policy formulation is based on the experience of South Korea that has successfully overcome Covid-19 in its country. By using descriptive research methods, using data sources from books, journals, and writings related to Covid-19. The massive distribution of Covid-19 in Indonesia has encouraged the government to formulate appropriate and accurate policies to address Covid-19 in Indonesia. In formulating the policy, it can be based on the experience of other countries that have been successfully applied. South Korea as one of the countries that have successfully overcome the spread of Covid-19 by utilizing technology should be used as an example of learning. South Korea utilizes state technology (smart city infrastructure) in tracking Covid-19 patients. Through this tracking process, the spread of Covid-19 can be reduced. For Indonesia, the South Korean experience regarding the use of various technologies to detect Covid-19 patients and their distribution is now important for Indonesia. Tracking via credit/debit card transactions, tracking cellphone history (calls, text message, Whatsapp, etc.), cellphone GPS tracking, tracking through social media (Instagram, Twitter, Facebook, etc.), as well as tracking on start-up applications such as Gojek and Grab will make it easier for the government to be able to detect and suppress the distribution of Covid-19. The development of Covid-19 applications will also be more comprehensive in dealing with Covid-19 in Indonesia